2022
DOI: 10.7759/cureus.29225
|View full text |Cite
|
Sign up to set email alerts
|

Severe Vitamin B12 Deficiency Presenting as Pancytopenia, Hemolytic Anemia, and Paresthesia: Could Your B12 Be Any Lower?

Abstract: Although severe vitamin B12 deficiency is rare in the United States, recent increases in the adoption of vegan lifestyles have led to a significant rise in the rates of B12 deficiency, along with its hematologic and neurologic sequelae, the latter of which is often irreversible.We describe a case of a 39-year-old male who presented with a several-month history of progressively worsening word-finding difficulties, shortness of breath, and a four-day history of bilateral hand numbness and tingling. Laboratory da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…However, peripheral smear revealed macrocytosis, elliptocytes, and hypersegmented neutrophils (Figure 1 ), suggestive of B12 deficiency. Vitamin B12 levels were undetectable, confirming the diagnosis of pseudo‐TMA caused by B12 deficiency, as described in previous case reports [ 1 , 2 , 3 ]. Neurological examination was normal.…”
Section: Figuresupporting
confidence: 84%
See 1 more Smart Citation
“…However, peripheral smear revealed macrocytosis, elliptocytes, and hypersegmented neutrophils (Figure 1 ), suggestive of B12 deficiency. Vitamin B12 levels were undetectable, confirming the diagnosis of pseudo‐TMA caused by B12 deficiency, as described in previous case reports [ 1 , 2 , 3 ]. Neurological examination was normal.…”
Section: Figuresupporting
confidence: 84%
“…Vitamin B12 levels were undetectable, confirming the diagnosis of pseudo-TMA caused by B12 deficiency, as described in previous case reports [1][2][3]. Neurological examination was normal.…”
supporting
confidence: 82%
“…Vitamin B12 deficiency can result in demyelination of the dorsal and lateral columns of the spinal cord causing subacute combined degeneration as evidenced by paresthesia, sensory deficits, ataxia, and weakness [ 3 ]. In patients with known vitamin B12 deficiency, common findings include anemia (37%), macrocytosis (54%), and hypersegmented neutrophils (32%); however, pancytopenia is a rare presentation and is only seen in 5% of patients [ 5 ]. Vitamin B12 is used in deoxyribonucleic acid (DNA) synthesis and is required for proper division of hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…With pernicious anemia, it is important to start treatment early. Although the anemia typically resolves in four to six weeks, neurologic symptoms can take several months to improve and in some cases be permanent [ 5 ]. Treatment of patients with pernicious anemia involves IM injections of vitamin B12 for improved bioavailability [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these reported pediatric cases of vitamin B12 deficiency, the patients presented with severe manifestations of the disease, including pancytopenia, hepatosplenomegaly, leukoerythroblastosis, and neurologic developmental regression secondary to known, documented nutritional deficiencies [5][6][7]. In similar cases within the adult population, it was concluded that a lifelong vegetarian or vegan diet rich in veggies, bread, and rice was the primary factor causing the underlying vitamin deficiency [8][9][10]. This is unlike our case in which past medical history, family history, and social history, even after a thorough review of the electronic medical record, were unremarkable in diagnosis.…”
Section: Discussionmentioning
confidence: 99%